2022
DOI: 10.1111/nuf.12714
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling beauty: Insight into being tattooed postmastectomy

Abstract: Background: It could be argued that mastectomy tattoos are being considered by some women in contemporary society as an alternative to breast reconstruction.Aim: To gain insight into the experience of "being" tattooed where breast(s) once occupied space, six women with mastectomy tattoos were interviewed.Methodology: The teachings of Gadamer's philosophical hermeneutics were engaged to better understand what it means "to be" tattooed postmastectomy.Results and Discussion: Discoveries include feeling sad and da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…There was a powerful narrative in Anjana’s description of the degrading nature of breast cancer surgery and how transformative the artistic tattooing of the chest had been in providing a metaphoric guard against the pain of the past. These findings, illuminating the transformative outcomes of artistic tattooing, align with those of Eschler et al (2018) , Reid-de Jong (2022) and Strübel and Jones (2017) .…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…There was a powerful narrative in Anjana’s description of the degrading nature of breast cancer surgery and how transformative the artistic tattooing of the chest had been in providing a metaphoric guard against the pain of the past. These findings, illuminating the transformative outcomes of artistic tattooing, align with those of Eschler et al (2018) , Reid-de Jong (2022) and Strübel and Jones (2017) .…”
Section: Discussionmentioning
confidence: 56%
“…There is a corpus of research describing the negative emotional and psychological impacts of breast cancer mastectomy surgery and scarring and how that influences women’s body image and sense of self ( Brunet et al, 2022 ; Hopwood and Hopwood, 2019 ; Piot-Ziegler et al, 2010 ). An emerging research area has shown that artistically tattooing the post-mastectomy body has potential to positively influence or change that post-cancer embodied experience ( Reid-de Jong, 2022 ; Reid-de Jong and Bruce, 2020 ; Strübel and Jones, 2017 ). In an effort to contribute to that emerging area of interest, the current study aimed to explore how artistically tattooing mastectomy scars change how women perceive their post-cancer body and how women experienced their evolving self from these often confronting and highly medicalised experiences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations